The Effect of Pick, List, Evaluate, Active, Supply, End (PLEASE) Strategy on Students’ Writing Ability in Developing Descriptive Paragraphs - Sari, Suci Anjar; Fatkurochman, Henri; Astutik, Indri (Journal of English Language and Education, 2023)
The purpose of this study was to look into the effect of the PLEASE (Pick, List, Evaluate, Activate, Supply, and End) approach on the development of paragraph writing skills. It attempted to look into the effect. In previous study, the research was conducted in areas outside East Java and this research was conducted in the area of East Java, to be precise at SMP Negeri 2 Genteng, Banyuwangi. Seventy-three EFL students from SMP Negeri 2 Genteng took part in the study and were divided into experimental and control groups. The researchers used a pre- and post-test on both groups to achieve the study's goal. The research was analyzed by comparing the pre-test and post-test of both group by using normality test, homogeneity test and independent sample t-test. The findings of the data analysis revealed that the PLEASE method had a significant effect on developing paragraphs.